2020
DOI: 10.21203/rs.3.rs-19604/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covariation of the gut microbiome with diet in Aves

Abstract: Background:Research over the past few decades has revealed a vital role for the gut microbiome in the health of various animals including birds. Multiple factors can influence the gut microbiome. Opportunistic feeding and multiple other environment factors can influence the results, and bias the conclusions, when wild animals are used to study the influence of phylogeny and diet on their gut microbiomes. Therefore, to study this question in this study, we collected fecal samples from 43 species of Aves at one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…However, its central role in the network suggests that further studies are required. Recently, Xiao et al (2020) compared the gut microbiome in different bird species and found that birds fed a corn-soybean basal diet showed a strongly interconnected microbial community with species from the classes Clostridia and Bacteroidia. In line with these findings, although the 155 genomes presented in this study constitute only a small sample of the GIT microorganisms, there was also a strong representation of bacteria in these classes in the network, with bacteria genera Alistipes, Ruminococcus, Fournierella, and Faecalicatena.…”
Section: Discussionmentioning
confidence: 99%
“…However, its central role in the network suggests that further studies are required. Recently, Xiao et al (2020) compared the gut microbiome in different bird species and found that birds fed a corn-soybean basal diet showed a strongly interconnected microbial community with species from the classes Clostridia and Bacteroidia. In line with these findings, although the 155 genomes presented in this study constitute only a small sample of the GIT microorganisms, there was also a strong representation of bacteria in these classes in the network, with bacteria genera Alistipes, Ruminococcus, Fournierella, and Faecalicatena.…”
Section: Discussionmentioning
confidence: 99%